The Role of Benina Airport in the Development of Eastern Part of Libya - F Salem , Prof.Salem; Bayou, Ms.Fatima (مجلة كلية الاداب, 2022)
The rationale for the choice of the problem of this study is based on the following points: the airport has undergone four historical development periods and the second period (1952- 1969) was the most important one, in which Benina and the other Libyan airports witnessed an unprecedented prosperity, where the State started to implement a series of economic and social plans. Through the study of population growth around the area of Benina, it was found that the airport did not contribute to the growth of the city as is customary known in most airports in the world. It has been shown through the studying of the compositional structure of the airport facilities and components that most of the departments of the airport suffer from worn out and lack of maintenance. The findings of the study showed also that the airport is currently suffering from a host of problems that had a negative impact on the efficiency of its operation; the most important of that is the noise brought about by the warplanes which cause great nuisance to residents living near a residential area of the airport, leading to ear and hearing problems for 32% of the total respondents surveyed in the study. In addition to the environmental effects on housing near the airport, this had led 33.5% of the total sample studied individuals to complain of disruptions in phone calls and cracks in the walls of houses. Thus, , in order to achieve the desired objectives perfectly, the officials and those interested in the field of airports and air transport in general must put the following important recommendations into consideration:- (1) More attention must be paid to the application of environmental legislation, in order to preserve the environment around the airport from the dangers arising from the mismanagement of Benina International Airport. (2) The officials of the civil aviation administration must separate between civil and military airplanes , in order to avoid problems arising from the joint use, which claimed the lives of passengers of flight No. 1103 heading to Tripoli in 1992. (3) The rehabilitation of the airport with the latest cutting-edge technology and means of moving belts and surveillance equipment and vehicles transporting passengers with sophisticated luggage and other modern technologies that help to accelerate the development of passenger traffic at the airport. (4) The management authority must unify security agencies operating within the airport, and determine the whereabouts and the allocation of special uniforms for each of them.